Biomarkers to identify ILD and predict lung function decline in scleroderma lung disease or idiopathic pulmonary fibrosis - Kennedy, Barry; Branagan, Peter; Moloney, Fiachra; Haroon, Muhammad; O'Connell, Oisin J; O'Connor, Terence M; O'Regan, Kevin; Harney, Sinead; Henry, Michael T (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: SSc-ILD and IPF demonstrate significant morbidity and mortality. Predicting disease progression is challenging in both diseases. Objectives: We sought a serum biomarker that could identify patients with SSc-ILD or IPF and prospectively predict short-term decline in lung function in these patients. Methods: 10 healthy controls, 5 SSc w/o ILD, 6 SSc-ILD and 13 IPF patients underwent venesection. An array of cytokines including KL-6, SP-D and MMP7 were measured. PFTs were obtained at baseline and six months. Cytokine measurements were correlated with PFTs. Results: KL-6 in IPF patients (633ng/ml, IQR 492-1675) was significantly elevated compared to controls (198ng/ml, IQR 52-360, p<0.01) and SSc w/o ILD patients (192ng/ml, IQR 0-524, p<0.05); KL-6 in SSc-ILD patients (836ng/ml, IQR 431-1303) was significantly higher than in controls (p<0.05). SP-D was significantly higher in IPF patients (542ng/ml, IQR 305-577) compared to controls (137ng/ml, IQR 97-284, p<0.01) or to SSc w/o ILD patients (169ng/ml, IQR 137-219, p<0.05). In comparison with controls (0.0ng/ml, IQR 0.0-0.6), MMP7 was significantly higher in both IPF patients (2.85ng/ml, IQR 1.5-3.6, p<0.05) and SSc-ILD patients (5.41ng/ml, IQR 2.6-7.2, p<0.001). Using a cut-off level of 459ng/ml for KL-6 and of 1.28ng/ml for MMP7, 18 out of 19 patients with ILD had a serum value of either KL-6 or MMP7 above these thresholds. For all ILD patients, baseline serum SP-D correlated with ΔFVC %pred over six months (r=-0.63, p=0.005, 95% CI -0.85 to -0.24). Conclusions: Combining KL-6 with MMP7 may be a useful screening tool for patients at risk of ILD. SP-D may predict short-term decline in lung function.